Revolution Collected and Curated Russian Revolution: Hope, Tragedy, Myths at the British Library. (2nd October 2018) - Rogatchevskaia, Ekaterina
ABSTRACT: This article discusses the theory of exhibition presentation as a genre, the specific issues of curatorial styles, and the distinct features of exhibitions in libraries. Based on my personal reflections on taking part in curating the Russin Revolution: Hope, Tragedy, Myths exhibition at the British Library, the article discusses the tension between the nature of collections held in libraries and their transformation when turned into an exhibition display, as well as the tension between the purpose of collecting for libraries and collecting for displays. It also presents the author's experience of the challenges and solutions that exhibitions in libraries normally face. As the number of exhibition projects in all kinds of libraries is growing, the library communities are looking toward a better understanding of how libraries' special and general collections can function in an exhibition environment and how information professionals can contribute to curatorial practices. Sharing experience about library exhibitions in the wider framework of art and museum curation will help to recognize exhibition curating as a requisite part of librarianship, which might change our perception of libraries and their relations with users now and in the future.